Phytoplankton biomass in northern lakes reveals a complex response to global change - Paltsev, Aleksey; Bergström, Ann-Kristin; Vuorio, Kristiina; Creed, Irena F.; Hessen, Dag Olav; Kortelainen, Pirkko; Vuorenmaa, Jussi; de Wit, Heleen A.; Lau, Danny C.P.; Vrede, Tobias; Isles, Peter D.F.; Jonsson, Anders; et al. (Elsevier, 2025)
Highlights • Spatial and temporal drivers of phytoplankton biomass in Fennoscandia • Long-term effects of global change on phytoplankton • Phytoplankton biomass is changing differently across Fennoscandia lakes. • Gonyostomum semen biomass is decreasing, while cyanobacterial biomass is increasing. • Spatial and temporal changes in phytoplankton have different underlying factors. Abstract Global change may introduce fundamental alterations in phytoplankton biomass and community structure that can alter the productivity of northern lakes. In this study, we utilized Swedish and Finnish monitoring data from lakes that are spatially (135 lakes) and temporally (1995-2019, 110 lakes) extensive to assess how phytoplankton biomass (PB) of dominant phytoplankton groups related to changes in water temperature, pH and key nutrients [total phosphorus (TP), total nitrogen (TN), total organic carbon (TOC), iron (Fe)] along spatial (Fennoscandia) and temporal (25 years) gradients. Using a machine learning approach, we found that TP was the most important determinant of total PB and biomass of a specific species of Raphidophyceae - Gonyostomum semen - and Cyanobacteria (both typically with adverse impacts on food-webs and water quality) in spatial analyses, while Fe and pH were second in importance for G. semen and TN and pH were second and third in importance for Cyanobacteria. However, in temporal analyses, decreasing Fe and increasing pH and TOC were associated with a decrease in G. semen and an increase in Cyanobacteria. In addition, in many lakes increasing TOC seemed to have generated browning to an extent that significantly reduced PB. The identified discrepancy between the spatial and temporal results suggests that substitutions of data for space-for-time may not be adequate to characterize long-term effects of global change on phytoplankton. Further, we found that total PB exhibited contrasting temporal trends (increasing in northern- and decreasing in southern Fennoscandia), with the decline in total PB being more ...